Strategi Pelestarian Bahasa Indonesia Sebagai Identitas Nasional Pada Generasi Z di Tengah Arus Globalisasi Digital - Syabilah, Firza; Bangun, Yogi Arifandi; Tanjung, Danar Ilyasa Zafin; Banjarnahor, Yurike N; Simanungkalit, Jhon Fawel; Rabbani, Rachmat Daffa; Pulungan, Hendra Kurnia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Amid the strong currents of digital globalization, the Indonesian language faces significant challenges, particularly from the dominance of foreign languages and the phenomenon of code-mixing among Generation Z. Nevertheless, technological advancement also provides opportunities to strengthen the sustainability of the national language. This study aims to examine the signifinance of the Indonesian language as a symbol of national identity and the strategies that can be applied to maintain it in the digital era. Using a literature study method, it was found that the main strategies include education, the positive use of digital media, and government policy support. In conclusion, the active role of all parties, especially Generation Z, is crucial to ensure that the Indonesian language remains sustainable and dignified in the eyes of the world.